The Use of Academic Assessment Instruments for Students with Intellectual Disability in Special Schools - Fauzi Nahwah Mujahid (Indonesian Journal of Disability Studies, 2019)
The concept of assessment for students with special need exists is to find and gather information on the children's obstacles and potentials. In the implementation of special education assessment, it is a need to understand the various aspects of assessing the ability of the child. The aim of this research is to analyze the use of assessment for students with special need in Surakarta city. This research uses a qualitative approach to the subject of as many as 50 teachers from 11 inclusion schools and special schools. The result of this research shows that 82% inclusive and special schools in Surakarta city do not have a proper standardization in the use of academic assessment instruments by teachers at the beginning of the learning process yet. Moreover, 55% of schools do not do an initial assessment and do only the assessment at mid and end time of the learning process. The impact of the problems, when teachers do the assessment, bring through the results of the assessment to not cover the skills that will be assessed by the teacher.